Modelagem evolucionária da dinâmica industrial (Parte 1): Concorrência, regimes tecnológicos e difus\~ao de conhecimento - José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Technological changes, when taken exogenously, would be represented by upward shifts in the production curve. The evolutionary approach of economic growth is an alternative to study technological change as endogenous and dynamic process, in which the accumulation of capital takes strategic role over time. This study aims to review the literature, analyzing evolutionary modeling of industrial dynamics. This work is divided into two parts. The first, addressed in this study, focus on the main models that treat the Schumpeterian competition, technological regimes and diffusion of new knowledge. The second, which will be analyzed in another paper, intend to explain technological trajectories, absorptive capacity and learning processes. These concepts are essential to understand the innovation in the economy and in the neo-schumpeterian thinking.
Keywords: B52; O3; O33; 330; evolutionary economics; technological change; innovation